Characterization and In Vitro and In Vivo Evaluation of Tacrolimus-Loaded Poly(ε-Caprolactone) Nanocapsules for the Management of Atopic Dermatitis - Guilherme dos Anjos Camargo; Leandro Ferreira; Diego José Schebelski; Amanda Martinez Lyra; Fernanda Malaquias Barboza; Bruna Carletto; Adriana Yuriko Koga; Betina Christi Semianko; Daniele Toniolo Dias; Leandro Cavalcante Lipinski; Andressa Novatski; Vijayasankar Raman; et al. (MDPI AG, 2021)
Background: Tacrolimus (TAC) is a drug of natural origin used in conventional topical dosage forms to control atopic dermatitis. However, direct application of the drug often causes adverse side effects in some patients. Hence, drug nanoencapsulation could be used as an improved novel therapy to mitigate the adverse effects and enhance bioavailability of the drug. Methods: Physicochemical properties, in vitro drug release experiments, and in vivo anti-inflammatory activity studies were performed. Results: TAC-loaded nanocapsules were successfully prepared by the interfacial deposition of preformed polymer using poly(ε-caprolactone) (PCL). The nanoparticulate systems presented a spherical shape with a smooth and regular surface, adequate diameter (226 to 250 nm), polydispersity index below 0.3, and suitable electrical stability (−38 to −42 mV). X-ray diffraction confirmed that the encapsulation method provided mainly the drug molecular dispersion in the nanocapsule oily core. Fourier-transform infrared spectra suggested that nanoencapsulation did not result in chemical bonds between drug and polymer. In vitro drug dissolution experiments showed a controlled release with a slight initial burst. The release kinetics showed zero-order kinetics. As per the Korsmeyer-Peppas model, anomalous transport features were observed. TAC-loaded PCL nanocapsules exhibited excellent anti-inflammatory activity when compared to the free drug. Conclusions: TAC-loaded PCL nanocapsules can be suitably used as a novel nano-based dosage form to control atopic dermatitis.